Domestic Devotions in Medieval and Early Modern Europe - Ryan, Salvador (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Domestic devotion has become an increasingly important area of research in recent years, with the publication of a number of significant studies on the early modern period in particular. This Special Issue aims to build on these works and to expand their range, both geographically and chronologically. This collection focuses on lived religion and the devotional practices found in the domestic settings of late medieval and early modern Europe. More particularly, it investigates the degree to which the experience of personal or familial religious practice in the domestic realm intersected with the more public expression of faith in liturgical or communal settings. Its broad geographical range (spanning northern, southern, central and eastern Europe) includes practices related to Christianity, Judaism and Islam. This Special Issue will be of interest to historians, art historians, medievalists, early modernists, historians of religion, anthropologists and theologians, as well as those interested in the history of material religious culture. It also offers important insights into research areas such as gender studies, histories of the emotions and histories of the senses.